An online experiment on cooperation and groupishness across urban districts - Martin Kesternich; Timo Goeschl; Johannes Lohse; Daniel Römer; Christiane Reif (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We present experimental evidence that illuminates the trade-off between efficiency considerations and social identity concerns in an inter-city multilevel public goods game. In total, 616 inhabitants of Heidelberg and Mannheim take part in an online experiment in which they can allocate an initial endowment between a private account, an excludable (local) public good, and a non-excludable (regional) public good. We vary the efficiency of the two public goods and find that participants substitute contributions away from the local to the regional public good if the latter is more efficient. To investigate the role of social identity considerations we compare a condition in which the group composition in unknown to a decision in which participants are informed that they share the local public good with three other participants from their own neighborhood. We do not find that a salient common social affiliation affects participants' behavior per se. If the common local affiliation is revealed through a label, only citizens perceiving a strong local identification adjust their contribution behavior and contribute more to the excludable local public good. Revealing the local affiliation becomes even more effective in a priming condition when participants are remembered of their common local affiliation before they indicate their contribution decision.
Keywords: C90; D70; H41; 330